Pembrolizumab plus lenvatinib or axitinib compared to nivolumab plus ipilimumab or cabozantinib in advanced renal cell carcinoma: a number needed to treat analysis. (2nd January 2022) - Santoni, Matteo; Rizzo, Alessandro; Mollica, Veronica; Rosellini, Matteo; Marchetti, Andrea; Fragomeno, Benedetta; Battelli, Nicola; Massari, Francesco
ABSTRACT: Introduction: Substantial paradigm shifts have been recently registered in metastatic renal cell carcinoma (mRCC), with combination therapies including immunotherapy showing unprecedented results. We performed number needed to treat (NNT) and number needed to harm (NNH) analyses to evaluate these approaches in mRCC. Areas covered: Clinical data of mRCC patients enrolled in four phase III trials were collected. The rates at 6, 12, 18, and 24 months for overall survival (OS), duration of response (DoR), and progression-free survival (PFS) were considered. At 6 months, the number of patients that should be treated to prevent one death with sunitinib was 20 for both pembrolizumab-lenvatinib or axitinib, 14 for nivolumab-cabozantinib, and 50 for nivolumab-ipilimumab. NNT was 100 (at 6 months) or >100 (at 12 and 18 months) for nivolumab-ipilimumab. The combinations reported peculiar and not superimposable safety profiles at the NNH analysis. Expert opinion: Although our results should be interpreted with caution, the analysis provides useful insight into the increasingly compelling interpretation of clinical trials. Immune combinations present clinically meaningful differences in terms of efficacy, with some treatments reporting different results at the NNT and the NNH analyses.